District Head Management in Community Empowerment in the West Marawola Sub-District Area, Sigi Regency - Maria Lea Frensy Bakarbessy; Rudin M (Jurnal Ragam Pengabdian, 2026)
The objectives of this study are (1) To identify and describe the District Head’s management in the community empowerment process in West Marawola District, Sigi Regency. (2) To analyze the form of coordination between the District Head, village governments, and community institutions in supporting community empowerment efforts in West Marawola District. (3) To identify and analyze the supporting and inhibiting factors of the District Head’s role in community empowerment in West Marawola District. This research is qualitative in nature with four selected informants. Data collection used observation, interview, and documentation techniques. The data analysis techniques used were (1) Data   Collection (2) Data Reduction (3) Data Presentation (4) Verification (5) Conclusion. Based on the research results and analysis conducted by the researcher, it is concluded that: (1) The District Head’s management in the community empowerment process in West Marawola District, Sigi Regency is highly strategic and multidimensional. The District Head functions as a coordinator, facilitator, supervisor, and overseer who ensures that community empowerment programs run in accordance with local needs and regional government policies. (2) The implementation of coordination between the District Head and the village government in community empowerment in West Marawola District runs quite effectively. The District Head plays the role of a liaison who directs, facilitates, and oversees the implementation of empowerment programs to align with regency government policies and community needs. (3) Supporting factors in community empowerment in West Marawola District include the active role of village governments, policy support related to village autonomy, the existence of community institutions, and the available natural and social resource potential. However, there are inhibiting factors such as limited human resources, limited budget, low community participation, and weaknesses in coordination among stakeholders.